Bangsawan Dayak’ of Sarawak - Nur Afifah Vanitha, Abdullah (International Conference on Linguistics, Literature and Culture, 2012)
Bangsawan is a Malay theatre with modern and traditional theatre elements in it. It was the first to use a proscenium stage and acting director to coach its actors, and at the same time maintained rituals of opening and closing of its performances. The Bangsawan shows were inspired by stories of aristocrats and artisans from the Middle East, India, Europe, China and Malaya, something which was close to home for the troupe as the term Bangsawan means people with noble blood (Nur Nina 1992, p.g. 19).